THE ROLE OF RADIATION PRESSURE IN THE NARROW LINE REGIONS OF SEYFERT HOST GALAXIES - Davies, Rebecca L.; Dopita, Michael A.; Kewley, Lisa; Groves, Brent; Sutherland, Ralph; Hampton, Elise J.; Shastri, Prajval; Kharb, Preeti; Bhatt, Harish; Scharwächter, Julia; Jin, Chichuan; Banfield, Julie; et al. (The Astrophysical journal, 2016)
ABSTRACT We investigate the relative significance of radiation pressure and gas pressure in the extended narrow line regions (ENLRs) of four Seyfert galaxies from the integral field Siding Spring Southern Seyfert Spectroscopic Snapshot Survey (S7). We demonstrate that there exist two distinct types of starburst-active galactic nucleus (AGN) mixing curves on standard emission line diagnostic diagrams, which reflect the balance between gas pressure and radiation pressure in the ENLR. In two of the galaxies the ENLR is radiation pressure dominated throughout and the ionization parameter remains constant (log U ∼ 0). In the other two galaxies radiation pressure is initially important, but gas pressure becomes dominant as the ionization parameter in the ENLR decreases from log U ∼ 0 to −3.2 log U −3.4. Where radiation pressure is dominant, the AGN regulates the density of the interstellar medium on kiloparsec scales and may therefore have a direct impact on star formation activity and/or the incidence of outflows in the host galaxy to scales far beyond the zone of influence of the black hole. We find that both radiation pressure dominated and gas pressure dominated ENLRs are dynamically active with evidence for outflows, indicating that radiation pressure may be an important source of AGN feedback even when it is not dominant over the entire ENLR.